PENDET DANCE’S MORAL VALUES IN TRI HITA KARANA PERSPECTIVE AS A MEDIA OF CHARACTER BUILDING EDUCATION FOR EARLY CHILDHOOD - Ni Luh Enita Maharani; Ni Luh Putu Wiardani Astuti (Proceeding of International Conference on Art, Language, and Culture, 2017)
Pendet dance is ladies dance which has function as dancers who bring ritual offering for the ancestors and Gods. Pendet dance is one of the ceremonial dances known by Balinese people commonly used in piodalan ceremony.The process of education that is perceived to be able to answer market demand is the concept of 'collaboration' between formal and non-formal education namely potential exploration through self-actualization. The synergy between formal and non-formal education can be a medium in mapping self-potential. Thus this synergy is able to create harmony of 'balancing' in a person.Non formal education is becoming the standard in character education such as Pendet dance for early childhood. The purpose is to introduce the sense, function and education media that can be reference for and character education values because there is moral values in the dance, the notion in Tri Hita Karana.